"Semi-straight sort of sex": class and gay community attachment explored within a framework of older homosexually active men - Chapple, M.J.; Kippax, S.; Smith, G. (Journal of homosexuality)
"M.J. Chapple; S. Kippax; G. Smith Fonds Suzan Daniel (FSD)"